RURAL CUSTOMER BEHAVIOUR TOWARDS ONLINE SHOPPING WITH SPECIAL REFERENCE TO THE RURAL AREAS IN THIRUVANANTHAPURAM DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The largest proportion of customers in India is residing in rural areas. The advancement in technology and the emergence of smartphones have mostly influenced the urban population but these developments made slight changes among the rural people. Rural customers are highly dependent upon agriculture and allied activities. So they are not much familiar with the advanced technology and do not have the facilities of urban people. According to the World Bank collection of development, indicators were reported the rural population at 65.07 percent in 2020. The present study aims to find the behaviour of rural customers towards online shopping.